2016
DOI: 10.14744/anatoljcardiol.2016.6885
|View full text |Cite
|
Sign up to set email alerts
|

An increase in epicardial adipose tissue is strongly associated with carotid-intima media thickness and atherosclerotic plaque, but LDL only with the plaque

Abstract: Objective:Carotid intima-media thickness (CIMT) is reliable marker of subclinical atherosclerosis and cardiovascular events. Until today, there was no study that investigated whether epicardial adipose tissue (EAT), which is a surrogate for lipid depot in a special visceral tissue or circulating lipids, is more important for CIMT and atherosclerotic plaque.Methods:Our study, having cross-sectional and prospective observational design, included 252 patients who were admitted to our outpatient clinic. EAT identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“… 4 - 6 , 13 - 15 Moreover, Hwang et al reported that EFT is related to the formation of non-calcified coronary plaque in asymptomatic individuals. 16 Similarly, it has been stated that EFT is associated with atherosclerotic plaque and CIMT by Kocaman et al 17 In our study, EFT and CIMT were also strongly correlated.…”
Section: Discussionsupporting
confidence: 83%
“… 4 - 6 , 13 - 15 Moreover, Hwang et al reported that EFT is related to the formation of non-calcified coronary plaque in asymptomatic individuals. 16 Similarly, it has been stated that EFT is associated with atherosclerotic plaque and CIMT by Kocaman et al 17 In our study, EFT and CIMT were also strongly correlated.…”
Section: Discussionsupporting
confidence: 83%
“…We did not find an association between PF and carotid or cerebral artery atherosclerosis. In contrast, previous studies have found an association between CIMT and epicardial fat [ 12 , 15 ], but data regarding cerebral arteries were not found in the literature.…”
Section: Discussionmentioning
confidence: 67%
“…We used morphometric measurements of atherosclerosis rather than using estimated atherosclerosis quantification [ 7 , 8 , 18 , 19 ]. Similarly, we used direct measurements to quantify the visceral fat instead of imaging methods [ 5 , 6 , 12 15 , 18 , 19 , 46 ]. Another strength was the larger sample size compared to previous autopsy studies that assessed a maximum of 116 individuals [ 7 , 8 , 18 20 ], allowing us to test the interaction between age and visceral fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data in humans suggest that EAT and PAT may be “beige” in morphology, with features of both WAT and BAT 11 13 . Measurements of EAT and PAT volume have suggested that the thickness of pericardial adipose tissue, which comprises both EAT and PAT, may serve as a risk factor and biomarker to predict the early stages of atherosclerosis and coronary heart disease (CAD) 14 16 . Given the different depot-specific gene expression profiles in “brown” adipocytes, the purpose of this study was to provide a better understanding of the putative thermogenic function of human EAT and PAT using tissues obtained from patients undergoing open heart surgery with and without CAD.…”
Section: Introductionmentioning
confidence: 99%